#TITLE_ALTERNATIVE# - PARDOMUAN (NIM 12206088); Pembimbing: Ir. Leksono Mucharam, M.Sc., Ph.D., EKASIH
Surfactant Injection is one of the Enhanced Oil Recovery methods. Surfactant is a surface's active agent that can reduce interfacial tension between oil and water. Interfacial tension is a function of molecules' attraction across the interface. Capillary forces exist because an interfacial tension (IFT) is present at the interface between two immiscible fluids. Surfactant is usable for reducing IFT and therefore reduce capillary forces that cause Sor (residual oil saturation) trapped in pores and can not be produced. The success of surfactant injection depends on several parameters. Injection's rate and Concentration of surfactant are important parameters to be analized. Because the combination of both is a function of surfactant's mass rate that will be injected into reservoir. From this research, we are able to know the contribution of each parameter in increasing the recovery factor and the good combination between injection rate and surfactant concentration to get the maximum oil recovery from the reservoir. Surfactant injection is not an inexpensive project, so we have to consider the benefit from this project. Therefore we have to consider the economic factor of this project before we inject surfactant into reservoir. By having a good combination of rate injection and concentration of surfactant, highest oil recovery and high benefit can be achieved through this project.